Microalbuminuria and Retinopathy among Hypertensive Nondiabetic Patients at a Large Public Outpatient Clinic in Southwestern Uganda. (6th June 2018) - Kangwagye, Peter; Rwebembera, Joselyn; Wilson, Tony; Bajunirwe, Francis
Abstract : Background . Routine testing of microalbuminuria and retinopathy is not done among patients with high blood pressure in resource-limited settings. We determined the prevalence of microalbuminuria and retinopathy and their risk factors among hypertensive patients at a large hospital in western Uganda. Methods . We consecutively recruited nondiabetic patients with hypertension at the outpatients' clinic over a period of 3 months. Spot urine samples were tested for urine albumin. Direct fundoscopy was done to assess retinal vasculature and optic disc for signs of hypertensive retinopathy. Logistic regression was done with retinopathy and microalbuminuria as primary outcomes. Results. We enrolled 334 patients and, of these, 208 (62.3%) were females, with median age of 55 years (range: 25–90). The prevalence of microalbuminuria was 59.3% (95% CI: 50.1–72.2) and that of retinopathy was 66.8% (95% CI: 58.6–76.5). The independent correlates of retinopathy and microalbuminuria were systolic blood pressure (SBP) > 140 mmHg (OR = 2.76, 95% CI: 1.29–5.93) and treatment with beta-blockers (OR = 2.16, 95% CI: 1.05–4.44). Use of ACEIs was unrelated to the study outcomes. Conclusion. The prevalence of retinopathy and microalbuminuria is high. Clinicians should aim for better control of blood pressure and routinely perform fundoscopy and urine albumin, especially for patients with poorly controlled blood pressure.